Sinergi Inovasi dan Tradisi dalam Pengembangan Pariwisata di Desa Adat Kemiren - Oktawirani, Panca (Yayasan Literasi Sains Indonesia, 2023)
Innovations and initiatives in village tourism continue to grow along with community involvement and participation in the development of tourism products and activities in the village. The Kencana Tourism Awareness Group in Kemiren village continues to strive to maintain its branding as a cultural village by renewing the tourism products and activities offered. This study used an explanatory approach, with data collected through interviews, observations and literature studies. The results of the study identified the types of innovations, the role of the parties, especially the management of Kemiren traditional village in sustainable tourism development by maintaining tradition and culture. Some strengthening of traditions and innovations are reflected in products, processes, management, marketing, and institutions, among others: 1) the inventory of types of innovation in Kemiren Traditional Village, in the form of strengthening product promotion, tour packages, crafts through digital systems as a result of creativity and hard work of youth, 2) The role of stakeholders in tourism development as planners, facilitators, motivators, and communicators through pokdarwis, BUMDES, traditional dance studios, art communities and village culinary specialties, 3) strengthening policies and drafting village regulations in the preservation of Gandrung culture, traditional houses, and Kemiren traditional clothing, through village regulations for the preservation of traditional houses and village regulations for clean water management systems, 4) Facilitating the strengthening of business quality and services through soft loans to the community and small and medium enterprises, strengthening the capacity of tour guides who emphasize the uniqueness and uniqueness of the Osing Kemiren tourism village, 5) co-creation between the community and visitors in the form of activities and tourist attractions sangrai ngopi, ngopi ten ewu, or gejog lesung.